2011
DOI: 10.1371/journal.pntd.0001310
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Synthetic Peptides for the Immunodiagnosis of Canine Visceral Leishmaniasis

Abstract: BackgroundVisceral leishmaniasis is the most severe form of leishmaniasis. Approximately 20% of zoonotic human visceral leishmaniasis worldwide is caused by Leishmania infantum, which is also known as Leishmania chagasi in Latin America, and disease incidence is increasing in urban and peri-urban areas of the tropics. In this form of disease, dogs are the main reservoirs. Diagnostic methods used to identify Leishmania infected animals are not able to detect all of the infected ones, which can compromise the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 44 publications
0
47
0
3
Order By: Relevance
“…Recently, Costa et al (27) performed ELISAs using single and mixed synthetic antigens from previously evaluated proteins, which showed high sensitivity in serum samples with low (95%) and intermediate (95%) antibody titers and high specificity (95%); the capacities of these synthetic antigen mixtures were not assayed against asymptomatic dogs, and crossreactivity assays were not performed. In addition, Faria et al (28) performed ELISAs using a mixture of synthetic antigens and obtained high sensitivity and specificity values (78.5% and 80%, respectively), but all of the synthetic antigens and the mixture exhibited high cross-reactivity with T. cruzi serum samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Costa et al (27) performed ELISAs using single and mixed synthetic antigens from previously evaluated proteins, which showed high sensitivity in serum samples with low (95%) and intermediate (95%) antibody titers and high specificity (95%); the capacities of these synthetic antigen mixtures were not assayed against asymptomatic dogs, and crossreactivity assays were not performed. In addition, Faria et al (28) performed ELISAs using a mixture of synthetic antigens and obtained high sensitivity and specificity values (78.5% and 80%, respectively), but all of the synthetic antigens and the mixture exhibited high cross-reactivity with T. cruzi serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…These antigens are relatively simpler and cheaper to produce than recombinant proteins. It also has been reported that the use of synthetic peptides (individually or in a mixture format), in comparison with the use of recombinant proteins, is able to increase the sensitivity and/or specificity of immunoassays for the serodiagnosis of parasitic diseases (26), such as canine and human visceral leishmaniasis (27,28).…”
mentioning
confidence: 99%
“…Only those future science group peptides that were simultaneously identified by the two programs were considered to be putative antigens for the development of immunoassays for cryptococcosis. This approach was based on the work of Faria et al, which showed that the use of the default scores of prediction software programs associated with the overlap predictions of more than one software program can be preferable to the use of a single type of prediction [40].…”
Section: Mapping B-cell Epitopesmentioning
confidence: 99%
“…Moreover, no false-positive result was observed when ROC curves were plotted, despite regular cross-reactive conditions, such as dogs that were infected with T. cruzi or E. canis and animals immunized with Leishmune or Leish-Tec Brazilian commercial vaccine. Recently, Faria et al (62) performed an ELISA using a mixture of synthetic antigens and obtained high sensitivity and specificity values (78.5% and 80%, respectively); however, all of the synthetic antigens and the mixture presented high cross-reactivity with serum samples from T. cruzi-infected dogs. In addition, Marcondes et al (63), who performed a rapid ELISA, showed a high rate of false-positive results in which high percentages of cross-reactivity occurred between Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%